2010
DOI: 10.1177/1534765610395663
|View full text |Cite
|
Sign up to set email alerts
|

Endurance is to be shown at the first blow: Social representations and reactions to traumatic experiences in the Gaza Strip.

Abstract: Research and clinical practice in the field of trauma has emphasized the construct of posttraumatic stress disorder. However, trauma has broader meanings that reflect its impact on the fabric of social life and that may be relevant to clinical understanding and intervention. This article illustrates the larger meanings of trauma with data from a pilot study designed to investigate the social representations of trauma and ways in which trauma is defined (i.e., meanings assigned to trauma) among Palestinians liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The same authors also note differences regarding Western perspectives that emphasize individual experience and personal success whereas in Arab contexts, group membership and service is tied to personal well-being. Afana (2012) and colleagues (Afana et al 2010) cautioned the uncritical application of the Western understanding of trauma to Palestinians as they may ignore locally derived expressions of distress and cultural meanings applied to traumatic events. In the future, additional qualitative analyses of questions concerning resilience, self-efficacy, and sub-factors of workplace empowerment may provide further detail to the preliminary interpretations offered herein.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…The same authors also note differences regarding Western perspectives that emphasize individual experience and personal success whereas in Arab contexts, group membership and service is tied to personal well-being. Afana (2012) and colleagues (Afana et al 2010) cautioned the uncritical application of the Western understanding of trauma to Palestinians as they may ignore locally derived expressions of distress and cultural meanings applied to traumatic events. In the future, additional qualitative analyses of questions concerning resilience, self-efficacy, and sub-factors of workplace empowerment may provide further detail to the preliminary interpretations offered herein.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…For example, an intervention exclusively targeting the domain of subjective mental health would provide a limited and inadequate response to the complex demands of a country experiencing an ongoing, irresolvable political conflict (Afana et al, 2010). In contrast, participative programs aimed at enabling community and societal resources, can be useful tools for promoting global health, human rights and social justice in the OPT (Veronese et al, 2010).…”
mentioning
confidence: 99%
“…Meaning-making can be understood as ‘a process in which people engage to reduce discrepancy’ (p259) or a search for comprehensibility and significance 68. Like this study, research conducted in the Gaza Strip revealed that severe adversity was described as musiba , meaning ‘a test by Allah’74 that requires endurance. Other studies have also shown that making meaning through aspects of religion can help people to overcome adversity, especially in the context of bereavement 75.…”
Section: Discussionmentioning
confidence: 74%